EFEKTIVITAS VIDEO PROFIL SEKOLAH SEBAGAI SARANA PROMOSI - Ni Wayan Meidariani; Made Henra Dwikarmawan Sudipa (Fakultas Bahasa Asing, 2024)
The community service partner in this article is elementary schools in West Denpasar District. This activity aims to help partners find solutions regarding student adequacy because the partner is a school with the smallest number of students compared to schools in the West Denpasar District. Based on the analysis, the team designed a school profile video. Profile videos are an effective medium for promotion. The content of the video profile consists of the school's vision, mission, history, and facilities. The results of this community service activity would become an inventory of school facilities and infrastructure as promotional material on social media. The method used in making the video is the observation method with recording and interview techniques. The making video process was divided into several steps. In the first step, the implementation team made observations by observing the surrounding conditions and interviewing one of the teachers at this school. This activity aims to make the material into a video. The second step is to cover the video by recording videos of school conditions and school facilities. The third step is the process of making and editing the video. The video is a product of this community service activity. This video was uploaded on partner social media to introduce the school to the community. This video is a promotional tool for actively sharing content on media sites. The results of this service activity have a long-term impact because it takes time to determine the effectiveness of the video in efforts to equalize students in West Denpasar District.